Fluorodeoxyglucose-positron emission tomography staging can replace bone marrow biopsy in Hodgkin's lymphoma. Results from Brazilian Hodgkin's Lymphoma Study Group - Juliano Júlio Cerci; Mateos Bogoni; Valeria Buccheri; Elba Cristina Sá de Camargo Etchebehere; Talita Maira Bueno da Silveira; Otavio Baiocchi; Carlos de Araujo Cunha Pereira Neto; Marcelo Tatit Sapienza; Jose Flavio Gomes Marin; José Cláudio Meneghetti; Yana Novis; Carmino Antonio de Souza; et al. (Hematology, Transfusion and Cell Therapy, 2018)
Objective: To investigate, in a large prospective multicenter study, whether 2-[18F]-fluoro-2-deoxy-d-glucose-positron emission tomography is sufficiently accurate to identify clinically important bone marrow involvement by Hodgkin's lymphoma to replace routine bone marrow biopsy in a developing tropical country. Methods: Patients newly diagnosed with Hodgkin's lymphoma were recruited from six cancer centers in Brazil. All were staged by the results of positron emission tomography/computed tomography that were centrally reviewed and by iliac crest bone marrow biopsy. Patients were classified as having marrow disease if they had lymphoma identified by marrow biopsy histology or had focal 2-[18F]-fluoro-2-deoxy-d-glucose marrow uptake that resolved following chemotherapy. Results: A total of 246 participants were recruited from six different centers and 62 (25.2%) were judged to have Hodgkin's lymphoma in the bone marrow. Positron emission tomography and biopsies were concordant in 206 patients (83%). Positron emission tomography correctly identified marrow disease in 59/62 patients (95.1%) and marrow biopsy in 25/62 patients (40.3%). In 22/62 (35.4%) patients, the two techniques were concordant in the diagnosis of marrow involvement. Of the forty discordant results, positron emission tomography found bone marrow involvement in 37 patients, upstaging 22 to stage IV and having an impact on therapeutic decision in nine cases given their reallocation from early to advanced stage. Three false negative positron emission tomography results were obtained with bone marrow biopsy giving positive findings. All three cases were classified as stage IV regardless of bone marrow findings implying no modification in the clinical management. The sensitivity, specificity and accuracy of positron emission tomography for detecting bone marrow disease were 95%, 100% and 98% and for bone marrow biopsy they were 40%, 100% and 84%, respectively. Conclusion: We conclude that positron emission tomography can replace marrow biopsy in Brazilian patients with Hodgkin's lymphoma without compromising clinical management. Keywords: Hodgkin's lymphoma, FDG-PET, Positron-emission tomography, Bone marrow biopsy, Lymphoma staging